STRATEGI PEMERINTAH DESA MEKARJAYA KECAMATAN CIKALONG WETAN KABUPATEN BANDUNG BARAT DALAM PENANGGULANGAN KEMISKINAN MELALUI PENGEMBANGAN ONE VILLAGE ONE PRODUCT - Setiawan, Agustina; Rokhmat, Dicky Febriansyah (Universitas Jenderal Ahmad Yani, 2025)
Poverty trends in Mekarjaya Village, Cikalong Wetan Subdistrict West Bandung Regency have tended to increase since 2019. This is related to the stunting treatment carried out by the Village Government with the Mekarjaya KB Village. However, the issue of poverty and stunting in Mekarjaya Village has not yet found the right strategy. This study aims at the Village Government's Strategy in Poverty Reduction and the Development of One Village One Product in Mekarjaya Village. The research used descriptive qualitative methods with data collection through interviews and observations. The results showed that the Village Government has not been able to identify holistically the potential of the village, especially in the agriculture, livestock and MSME sectors. Mekarjaya Village has the potential of clove commodities, but there are still no efforts related to value chain development, and marketing. Similarly, cassava commodities are processed into cassava chips. Recommendations from the Research Team that these strategies are not optimal enough to improve the economy of residents to get out of poverty and stunting cases. In this scope, the research team tries to formulate a strategy that can be carried out by Mekarjaya Village in managing the village's potential, namely by intervention by the village government.